lmpact of reafforestation with Eucalyptus globulus La bi l l . on the edaphic collembolan fauna of Serra de Monchique ( Algarve , Portugal ) - Barrocas, H M; Gama, M M; Sousa, J P; Ferreira, C S (Miscel.lania Zoologica, 1998)
lmpact of reafforestation with Eucalyptus globulus Labill. on the edaphic collembolan fauna of Serra de Monchique (Algarve, Portugal).- Native forests in Portugal have been gradually replaced by Eucalyptus globulus plantations. This exotic tree has been referred as a major factor of ecosystem disturbance (Gama et al. 1989, 1991, 1994, 1995; Sousa & Gama, 1994; Vasconcelos et al., 1994). The authors compared edaphic Collembola populations occurring in coppices of Quercussuber L. and Q. canariensis Willd. with those from stands of Eucalyptusglobulus Labill. from Serra de Monchique, to evaluate the effects of reafforestation with this exotic tree. The total analysis of data shows a rupture in the collembola communities associated with eucalyptus. Oak biotopes usually present higher values of diversity and species richness, with a greater total number of species and also more exclusive andlor preferential species than eucalyptus biotopes. No significant differences were detected among the different biotopes in terms of mean number of individuals. However, the abundance of individuals in eucalyptus biotopes results mainly from the presence of a few species which are represented by a great number of specimens, making up more than 85% of the individuals on eucalyptus sites
Keywords: Algarve; Collembola; Eucalyptus globulus; Q. canariensis; Quercus suber; REAFFORESTATION

Effects of introduced exotic tree species on Collembola communities: The importance of management techniques - Sousa, J P; Vingada, J V; Barrocas, H; DaGama, M M (PEDOBIOLOGIA, 1997)
Studies of the impact of the substitution of autochthonous forests by plantations of exotic tree species (a quite common phenomenon in Southern European countries) on soil arthropod communities (mainly Collembola and Acarina) generally deal with the effects of the exotic species per se and disregard the management techniques used. In this study the impact of the introduced Eucalyptus globulus on the Collembola communities of Quercus ilex ballota and Quercus suber stands was analysed. Since the autochthonous tree species are similar (in terms of leaf type and the ability to produce litter) the main objective was to examine the effects of the different management techniques used in the two plantations of Eucalyptus. (i) There is a significant difference in management techniques used in the Eucalyptus plantations leading to differences in habitat configuration: the plantation associated with the Helm-Oak stand is used for cellulose paste production, with periodic removal of the shrub and herbaceous layers; the other plantation, close to the Cork-Oak stand, is not managed at all, presenting an abundant shrub layer. (ii) in both cases, the substitution of the Oak species by Eucalyptus caused a disruption of the Collembola communities, although it was more pronounced in e. ilex ballota vs E. globulus (station 1) than in e. suber vs E. globulus (station 2). The number of individuals, the number of taxa and diversity parameters are in most cases greater under Oak species but more evident in station 1. (iii) Given these results, the influence of the factor `'management technique-habitat configuration'' in analysing and interpreting effects of exotics on soil arthropod communities is discussed.
IX International Colloquium on Apterygota, DUBLIN, IRELAND, 1996
Keywords: Collembola community disruption; EUCALYPTUS; Quercus illex; Quercus suber

RUPTURE IN A COLLEMBOLA COMMUNITY STRUCTURE FROM A QUERCUS-ROTUNDIFOLIA LAM FOREST DUE TO THE REAFFORESTATION WITH EUCALYPTUS-GLOBULUS LABILL - Sousa, J P; DaGama, M M (EUROPEAN JOURNAL OF SOIL BIOLOGY, 1994)
Here we compare Collembola populations from a Quercus rotundifolia forest and an Eucalyptus globulus plantation. The overall analysis of data (using both diversity and similarity measures) have shown clear signs of rupture on the structure of collembola populations, with the fauna associated with the Quercus stand being richer (in exclusive and preferential species) and more abundant than the one connected with the Eucalyptus. Data also reflects the faunal stratification between organic and mineral horizons, with the majority of species being associated with upper soil layers in detriment of mineral horizon. These disruptions may be related to profound alterations of habitat characteristics, particularly the frequent removal of shrub vegetation and leaf layer, result of the forestry practices connected with the preparations and management of the eucalyptus plantation.
Keywords: Collembola; EUCALYPTUS; holm-oak; REAFFORESTATION